A new species of Paracanthonchus Micoletzky, 1924 and a known species of Paracyatholaimus Micoletzky, 1922 (Nematoda, Cyatholaimidae, Paracanthonchinae) from polluted intertidal sand in Scotland. - Vadhyar, K. J. (Cah. Biol. mar., 1980)
Locality: NA; Cabinet:
Locality: NA; Cabinet:; NeMys doc_id: 7289